2012
DOI: 10.1172/jci65883
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure influences end-stage renal disease of Cd151 knockout mice

Abstract: In the second paragraph of the Introduction, the final two sentences were incorrect. The correct sentences are below. Finally, individuals with non-type O blood have decreased clearance of von Willebrand factor (vWF). Since FVIII circulates in plasma bound to vWF, an increase in plasma vWF is also associated with increased levels of FVIII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…11 The mechanisms for these glomerular abnormalities are well defined using laminin-binding integrin and CD151-null mice. 4,12 CD151-null mice present with FSGS, similar to that observed in humans carrying nonsense mutations in CD151. The degree of glomerulosclerosis in these mice is similar to that of mice lacking the integrin a3 subunit in podocytes and is related to podocyte loss.…”
Section: The Laminin Receptorssupporting
confidence: 67%
“…11 The mechanisms for these glomerular abnormalities are well defined using laminin-binding integrin and CD151-null mice. 4,12 CD151-null mice present with FSGS, similar to that observed in humans carrying nonsense mutations in CD151. The degree of glomerulosclerosis in these mice is similar to that of mice lacking the integrin a3 subunit in podocytes and is related to podocyte loss.…”
Section: The Laminin Receptorssupporting
confidence: 67%
“…[27][28][29] Global or podocyte-specific deletion of either subunit leads to proteinuria and early death in animals. 28,29,49 Additionally, we and others have recently shown that podocyte injury leads to reduced levels of active b1 in mice and patients, 30,33 which suggests that preventing loss of active b1-integrin levels in podocytes might be protective. Using novel small molecule agonists of b2 integrin CD11b/CD18, we have previously shown that such pharmacologic activation of integrins in vivo is a new, therapeutically relevant mechanism for targeting this family of adhesion receptors.…”
Section: Discussionmentioning
confidence: 90%
“…To date, it has been reported that CD151 KO mice have renal dysfunction (in the FVB strain) (26)(27)(28), impaired pathologic angiogenesis (15), delayed wound closure (29), and deficiencies in platelet aggregation (30). However, the involvement of CD151 in lung diseases remains unclear; this is the first report implicating CD151 in protection against pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 95%